Identification of acetylated diether lipids in halophilic Archaea. Issue 3 (9th June 2022) - Kropp, Cosimo; Lipp, Julius; Schmidt, Anna Lena; Seisenberger, Christina; Linde, Mona; Hinrichs, Kai‐Uwe; Babinger, Patrick
Abstract: As a hallmark of Archaea, their cell membranes are comprised of ether lipids. However, Archaea‐type ether lipids have recently been identified in Bacteria as well, with a somewhat different composition: In Bacillales, sn ‐glycerol 1‐phosphate is etherified with one C35 isoprenoid chain, which is longer than the typical C20 chain in Archaea, and instead of a second isoprenoid chain, the product heptaprenylglyceryl phosphate becomes dephosphorylated and afterward diacetylated by the O ‐acetyltransferase YvoF. Interestingly, database searches have revealed YvoF homologs in Halobacteria (Archaea), too. Here, we demonstrate that YvoF from Haloferax volcanii can acetylate geranylgeranylglycerol in vitro. Additionally, we present the first‐time identification of acetylated diether lipids in H. volcanii and Halobacterium salinarum by mass spectrometry. A variety of different acetylated lipids, namely acetylated archaeol, and acetylated archaetidylglycerol, were found, suggesting that halobacterial YvoF has a broad substrate range. We suppose that the acetyl group might serve to modify the polarity of the lipid headgroup, with still unknown biological effects. Abstract : Archaea‐type ether lipids have been found recently in Bacillales. They are monoether lipids with a C35 isoprenoid chain and are diacetylated by the O ‐acetyltransferase YvoF. Phylogenetic studies implied that YvoF homologs also occur in Halobacteria (Archaea). Here we show that YvoF from Haloferax volcanii has ether‐lipid‐specific acetyltransferase activity in vitro. Furthermore, we provide a mass spectrometric identification of acetylated archaeol and acetylated archaetidylglycerol in H. volcanii and Halobacterium salinarum for the first time.